Resilience of the elderly of the “Cristo Rey” Gerontological Day Center against the abandonment of their relatives - Aveiga Macay, Vicenta Inmaculada Ramona (2020)
The objective of this study was to demonstrate the resilience of older adults at the ¨Cristo Rey¨ Gerontological Day Center against abandonment by their relatives. To carry out the research process, a bibliographic review of several scientific articles was developed from which relevant information was obtained. on resilience in old age. The descriptive research allowed to explain the reality of the older adults of the institution. The qualitative-quantitative approach was used by analyzing the techniques of the interview carried out with twenty older adults who attend the center daily and a questionnaire of six questions to fifty older adults who are registered in it, where the results obtained could show that in the aging process the elderly in the city of Portoviejo is emotionally, physically and mentally affected due to the abandonment of their relatives, therefore the work of the social worker of the Day Center "Gerontológico Cristo Rey" is to know and transform the reality of the same in such a way that it is necessary to possess the greatest amount of data through to carry out a good diagnosis and orientation that allows to respond to the needs according to the available resources and thus promote active aging.